Inhibition of CREB activity in the dorsal portion of the striatum potentiates behavioral responses to drugs of abuse - Fasano, Stefania; Pittenger, Christopher; Brambilla, Riccardo (Frontiers in Behavioral Neuroscience, 2009)
The striatum participates in multiple forms of behavioral adaptation, including habit formation, other forms of procedural memory, and short and long-term responses to drugs of abuse. The CREB family of transcription factors has been implicated in various forms of behavioral plasticity, but its role in the dorsal portion of the striatum-has been little explored. We previously showed that in transgenic mice in which CREB function is inhibited in the dorsal striatum, bidirectional synaptic plasticity and certain forms of long-term procedural memory are impaired. Here we show, in startling contrast, that inhibition of striatal CREB facilitates cocaine- and morphine-place conditoning and enhances locomotor sensitization to cocaine. These findings propose CREB as a positive regulator of dorsal striatum-dependent procedural learning but a negative regulator of drug-related learning.